2016
DOI: 10.1016/j.jbiotec.2016.02.017
|View full text |Cite
|
Sign up to set email alerts
|

Complete genome of Pseudomonas sp. strain L10.10, a psychrotolerant biofertilizer that could promote plant growth

Abstract: Complete genome of Pseudomonas sp.strain L10.10, a psychrotolerant biofertilizer that could promote plant growth.Journal of Biotechnology http://dx.doi.org/10. 1016/j.jbiotec.2016.02.017 This is a PDF file of an unedited manuscript that has been accepted for publication. As a service to our customers we are providing this early version of the manuscript. The manuscript will undergo copyediting, typesetting, and review of the resulting proof before it is published in its final form. Please note that during t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 12 publications
0
8
0
Order By: Relevance
“…Pseudomonas , See‐Too et al . ()) and numerous studies have reported bacterial genera, such as Polarmonas , Flavobacteria and Sphingobacteria , living in close association with Chloromonas and Chlamydomonadaceae (Hoham & Duval, ; Komárek & Nedbalová, ; Hisakawa et al ., ; Lutz et al ., , , ; Hamilton & Havig, ). There were also a large number of OTUs that could not be assigned to a genus or species, implying that the communities in the Antarctic snow packs are yet to be fully identified, characterised and incorporated into public databases such as Silva (Quast et al ., ).…”
Section: Discussionmentioning
confidence: 99%
“…Pseudomonas , See‐Too et al . ()) and numerous studies have reported bacterial genera, such as Polarmonas , Flavobacteria and Sphingobacteria , living in close association with Chloromonas and Chlamydomonadaceae (Hoham & Duval, ; Komárek & Nedbalová, ; Hisakawa et al ., ; Lutz et al ., , , ; Hamilton & Havig, ). There were also a large number of OTUs that could not be assigned to a genus or species, implying that the communities in the Antarctic snow packs are yet to be fully identified, characterised and incorporated into public databases such as Silva (Quast et al ., ).…”
Section: Discussionmentioning
confidence: 99%
“…The complete genome of strain L10.10 T has been previously sequenced, enabling the discovery of various genes encoding for plant growth promoting properties and plant disease prevention attributes [45]. The draft genomes of strains A4R1.5 and A4R1.12 were obtained in this study in order to perform whole genome sequence analysis.…”
mentioning
confidence: 99%
“…Lz4W, Pseudomonas sp. L.10.10, and P. deceptionensis LMG25555; [50,52,54]. The P. aeruginosa strains were also the most divergent and ancestral branch among the set.…”
Section: Genetic Relationships and Pan-genome Analysismentioning
confidence: 95%
“…GC01 also closely resembles Pseudomonas sp. L.10.10 [52], with a 91% sequence identity, followed by an 85% sequence identity to P. fragi DBC [53] and two strains of P. deceptionensis LMG25555 and DSM26521 [54,55]. Interestingly, the strains with the higher similarity to Pseudomonas sp.…”
Section: Genetic Relationships and Pan-genome Analysismentioning
confidence: 98%